2009
DOI: 10.1089/apc.2008.0186
|View full text |Cite
|
Sign up to set email alerts
|

Women's Opinions about Routine HIV Testing During Pregnancy: Implications for the Opt-Out Approach

Abstract: The 1995 United States Public Health Service (USPHS) recommendation regarding HIV testing for pregnant women was revised in 2003 calling for routine HIV testing for pregnant women with patient notification. Routine testing (opt-out screening) offers women the opportunity to decline HIV testing but eliminates the requirement of pretest counseling and separate written consent. To assess women's opinions about the opt-out approach to HIV testing during pregnancy, a cross-sectional survey was conducted in May-June… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 15 publications
0
8
0
2
Order By: Relevance
“…The standards defined by guidelines on testing, such as informing clients, obtaining consent, and providing information, are not especially exacting, and can be achieved in most settings. Other studies, such as in the United States [33],[34] and in Egypt [35], have reported similarly high levels of service provision ad satisfaction.…”
Section: Discussionmentioning
confidence: 66%
“…The standards defined by guidelines on testing, such as informing clients, obtaining consent, and providing information, are not especially exacting, and can be achieved in most settings. Other studies, such as in the United States [33],[34] and in Egypt [35], have reported similarly high levels of service provision ad satisfaction.…”
Section: Discussionmentioning
confidence: 66%
“…There are unique opportunities to test patients who visit the emergency department or urgent care but might not otherwise seek testing [4-7], and hospital-wide routine HIV screening has been shown to be a valuable tool for identifying new infections and preventing missed opportunities to diagnose individuals of unknown status [8,9]. These testing opportunities can be driven by symptoms, which may indicate acute HIV infection [10] or by the patient care situation (e.g., pregnancy) [11,12]. In caring for patients who are sick, ready for discharge, or in labor, there can be a premium on rapid turnaround time.…”
Section: Introductionmentioning
confidence: 99%
“…Expansion of routine HIV screening in prenatal care settings (Podhurst, Storm, & Dolgonos, 2009), primary care clinics (Cook & Berkenblit, 2009), urgent care centers , emergency departments (Merchant et al, 2009), community health centers (Cunningham et al, 2009), outpatient clinics (Anaya et al, 2008), and corrections facilities (Beckwith et al, 2011;Kavasery et al, 2009aKavasery et al, , 2009b has been documented. Further expansion is needed to improve the potential benefits of early detection.…”
Section: Introductionmentioning
confidence: 99%